Shiver - Jackson, Lisa. (New York : Zebra Books, 2006)
Detective Reuben "Diego" Montoya must team up with the prime suspect in a murder case to catch a serial killer who is keeping New Orleans in the grip of fear, an investigation that leads them to an abandoned asylum where unspeakable evil awaits them.
Keywords: Montoya, Reuben (Fictitious character) -- Fiction; Serial murders -- Fiction; Asylums -- Fiction; New Orleans (La.) -- Fiction; Romantic suspense fiction; Mystery fiction